Measurements of Higgs-boson decays to leptons with the ATLAS detector - Lara Katharina Schildgen on behalf of the ATLAS Collaboration (SciPost Physics Proceedings, 2019)
Since its discovery in 2012, the Higgs boson has served as an important probe for precision measurements of the Standard Model and for searches for new physics beyond the Standard Model. One major goal of the LHC is the precise measurement of the Higgs Yukawa couplings to fermions. The latest ATLAS results of measurements of the Higgs boson decaying to leptons are presented, namely the cross-section measurement of the Higgs boson decay to two tau leptons and the searches for the di-muon decay and lepton-flavour-violating decays of the Higgs boson.